First-line chemotherapy in advanced intra-abdominal well-differentiated/dedifferentiated liposarcoma: an EORTC Soft Tissue and Bone Sarcoma Group retrospective analysis - Stacchiotti, Silvia; Van der Graaf, Winette T. A.; Sanfilippo, Roberta G.; Marreaud, Sandrine I.; Van Houdt, Winan J.; Judson, Ian R.; Gronchi, Alessandro; Gelderblom, Hans; Litiere, Saskia; Kasper, Bernd (Cancer, 2022)
BACKGROUND No prospective trial with anthracycline-based chemotherapy has individually assessed response in a well-differentiated (WD)/dedifferentiated (DD) liposarcoma patient cohort. We conducted a retrospective analysis of first-line chemotherapy in liposarcoma of intra-abdominal origin (IA-LPS) in patients who had entered the European Organisation for Research and Treatment of Cancer (EORTC)/Soft Tissue and Bone Sarcoma Group (STBSG) trials. METHODS We searched for all adult patients treated with first-line chemotherapy for advanced IA-LPS in the EORTC STBSG phase 2 and 3 trials from 1978. Treatment was aggregated into 5 groups: anthracycline alone, ifosfamide alone, doxorubicin plus ifosfamide (D+IFO), doxorubicin/cyclophosphamide/vincristine/dacarbazine, and “other” (brostallicin, trabectedin). Response was assessed prospectively by Response Evaluation Criteria in Solid Tumors or World Health Organization criteria. Progression-free survival (PFS) and overall survival (OS) were computed by Kaplan-Meier method. RESULTS A total of 109 patients with IA-LPS from 13 trials were identified (104 evaluable for response). Overall, there were 10/109 (9.2%) responders: 3/48 (6.3%) in the anthracycline alone group, 2/15 (13%) in the ifosfamide alone group, and 4/18 (22%) in the D+IFO group. At the 10-month median follow-up (interquartile range, 6-24), the median OS was 19 months (95% CI, 15-21) and median PFS 4 months (95% CI, 3-6). D+IFO achieved a not statistically significant longer median PFS (12 months) and median OS (31 months) than observed with other regimens. Univariate/multivariate analysis did not identify prognostic factors. CONCLUSIONS Cytotoxic chemotherapy, in particular anthracycline alone, had marginal activity in advanced IA-LPS. Ifosfamide-containing regimens showed higher activity, although it was not statistically significant and in a small number of cases, with the combination of doxorubicin and ifosfamide appearing to be the more active regimen available in fit patients. This series provides a benchmark for future trials on new drugs in WD/DD liposarcoma.;
Gesehen am 06.11.2023